2015
DOI: 10.1016/j.ajo.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Grading of Anaplasia in Retinoblastoma

Abstract: Purpose To determine whether the degree of tumor anaplasia has prognostic value by evaluating its correlation with high-risk histopathologic features and clinical outcomes in a series of retinoblastoma patients. Design Retrospective clinicopathologic study. Methods The clinical and pathologic findings in 266 patients who underwent primary enucleation for retinoblastoma were reviewed. The histologic degree of anaplasia was graded as retinocytoma, mild, moderate, or severe as defined by increasing cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 38 publications
4
48
1
1
Order By: Relevance
“…In some animals, neuroblastic Homer Wright rosettes were present. In Rb/TET-MYCN mice, tumor cells were somewhat larger and more often elongated, angular, or molded together (Supplemental Figure 1B) anaplastic features that have been associated with MYCN amplification in human retinoblastoma and worse clinical outcomes (3,31). We found that anaplastic changes were even more prominent in Rb/p107/TET-MYCN tumors (Supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 64%
“…In some animals, neuroblastic Homer Wright rosettes were present. In Rb/TET-MYCN mice, tumor cells were somewhat larger and more often elongated, angular, or molded together (Supplemental Figure 1B) anaplastic features that have been associated with MYCN amplification in human retinoblastoma and worse clinical outcomes (3,31). We found that anaplastic changes were even more prominent in Rb/p107/TET-MYCN tumors (Supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 64%
“…84–86 Emerging evidence indicates that high grade anaplasia (loss of differentiated characteristics) may be a risk factor for metastasis and death. 87 High-risk features by the Murphree IIRC 78 were observed in 15–33% of Group D and 50–61% of Group E eyes, 85,88 , but by the Shields IIRC (which classifies less affected D eyes as E), only 24–39% 89 of Group E eyes showed high risk. Adjuvant systemic chemotherapy after high-risk features are observed in an enucleated eye may reduce risk of metastatic relapse.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 98%
“…The grading of cellular anaplasia and nuclear morphometry has recently been shown to have prognostic significance in the absence of high-risk histologic features. 32 The benign variant retinocytoma consists of well-differentiated cells often with associated calcifications. Retinocytoma cells have small, round, bland nuclei and abundant cytoplasm.…”
Section: Pathology Of Retinoblastomamentioning
confidence: 99%